Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/21501203.2017.1383318
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radical scavenging active components in the fermented mycelia of Ophiocordyceps formosana

Abstract: The rates of 1,1-diphenyl-2-picryhydrazyl (DPPH)-free radical scavenging and hydroxyl radical eliminating were employed as indexes to qualitatively and quantitatively analyse the radical scavenging activity of the extracts with different solvents from fermented mycelia of Hirsutella huangshanensis RCEF0868, the anamorph of Ophiocordyceps formosana (FMOF). The results showed that both the aqueous extract and the methanol extract had significant radical scavenging activity. The half maximal inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…IC 50 values of hydroxyl inhibitory activity of aqueous and methanol extracts of mycelia of Ophiocordyceps formosana were 1.23 mg/mL and 2.91 mg/mL, respectively. 16 In comparison with the antioxidant activity of other Cordyceps species collected from different places, the ABTS radical scavenging activity of EPS from O. sinensis in this study was higher than that of the species reported by Shamar et al 15 and the species (except C. sinensis ) collected in Vietnam reported by Phuong-Tham Ho-Thi et al 14…”
Section: Resultscontrasting
confidence: 68%
“…IC 50 values of hydroxyl inhibitory activity of aqueous and methanol extracts of mycelia of Ophiocordyceps formosana were 1.23 mg/mL and 2.91 mg/mL, respectively. 16 In comparison with the antioxidant activity of other Cordyceps species collected from different places, the ABTS radical scavenging activity of EPS from O. sinensis in this study was higher than that of the species reported by Shamar et al 15 and the species (except C. sinensis ) collected in Vietnam reported by Phuong-Tham Ho-Thi et al 14…”
Section: Resultscontrasting
confidence: 68%
“…This is unique and explains why 2 appeared exclusively in the 5-exposed cultivation of both AO-rugGH and SC-RC01-rugGH cotransformants, rather than the cocultures of AO-rugH plus AO-rugG, or SC-BJ5464-rugH with SC-RC01-rugG, transformants (Figure 5). Such a cascade mechanism explains why, in nature, rugulosin A ( 2) is normally produced together with skyrin (1), 21,23,24,26,27 but not vice versa. 18,20 In alignment with the observation, the genomes of 1and 2-coproducing fungi contain the rugG and rugH homologues linked closely or contiguously (Tables S13−S16 and Figure S10), whereas no rugH homologue was found in that of Cyanodermella asteris (Figure S11), which generates 1 without yielding 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The potent bioactivities and unique structures of 1 and 2 have spurred their chemical synthesis. Surprisingly, the knowledge regarding their biosynthesis remains limited to the isotope feeding tests (performed half a century ago , ) and the bioinformatic prediction of the skyrin ( 1 ) biosynthetic cluster that awaits experimental verification . Skyrin ( 1 ) and rugulosin A ( 2 ) have been individually isolated from a broad range of taxonomically distant fungi (e.g., 1 from Cyanodermella asteris , Talaromyces islandicus , Dermocybe icterinoides , and T. rugulosus ; 2 from T. rugulosus , Ophiocordyceps formosana , Chrysoporthe sp. SNB-CN74, and Phialocephala scopiformis ).…”
Section: Introductionmentioning
confidence: 99%
“…It was expected that both fractions would display similar DNA protective properties assessed by this method since their radical scavenging activity was similar against DPPH (Table 3) and DNA single strand breaks in the DNA topology assay are due to the radical (hydroxyl radical) generated by FeSO 4 (Ševčovičová et al, 2015). The differences may be due to different scavenging potential against different radicals as it has been previously shown with skyrin, which exhibited scavenging activity against DPPH and no activity against hydroxyl radical (Li et al, 2017). Moreover, as iron-chelating activity would avoid reactivity of Fe 2+ , and hence DNA damage, DNA protecting activity might also be due to metal-chelating activity, besides scavenging of radicals.…”
Section: Genotoxicity Potential and Antigenotoxic Activitymentioning
confidence: 95%